N-acetyl-cysteine Reduces Neointimal Thickening and Procoagulant Activity after Balloon-induced Injury in Abdominal Aortae of New Zealand White Rabbits - Ghigliotti, Giorgio; Mereto, Eugenio; Eisenberg, Paul R.; Martelli, Antonietta; Orsi, Patrizia; Sini, Daniela; Spallarossa, Paolo (Thrombosis and Haemostasis, 2001)
Background: Procoagulant activity and oxidative stress generated by balloon injury to normal vessels promote the migration of medial smooth muscle cells and their proliferation in the intima. We hypothesised that administering levo N-acetyl-cysteine (NAC) i.v. at the time of injury, and s.c. before and after injury would reduce neointimal formation 4 weeks later and would regulate procoagulant activity in vessels with neointima undergoing ballooning a second time. Methods and Results: at the time of injury rabbits received: NAC, unfractionated heparin (HEP) or both (NAC + HEP). Neointimal thickening at 28 days, calculated as the ratio between the intimal and medial area, was attenuated after NAC, HEP and NAC+HEP by 39%, 30% and 47% respectively when compared to untreated injured animals (CONTROLS) (p 0.05). At 28 days, bound thrombin activity and platelet adhesion 1 h after a repeated balloon injury decreased in animals receiving NAC, HEP and NAC+HEP by 54%, 63% and 64% for thrombin activity (p 0.05 vs CONTROLS), and by 56%, 66% and 75% respectively for 111Indium-platelet deposition (p 0.05 vs CONTROLS). Conclusions: NAC in-vivo was effective in reducing neointimal thickening and procoagulant response after balloon injury.
Keywords: Levo N-acetyl-cysteine; thrombin; tissue factor; neointima; rabbit